Comparison on disinfection in water treatment system in conventional and ozonation system / Azizah Mohd Yusoff - Mohd Yusoff, Azizah (1996)
Urbanisation and commercial development lead to higher demand of water. Public awareness and health conscious has given a task to Water Authority to enhance the quality of treated water. The challenged faced by Water Authority is the deteriorating of the sources of raw water from the rivers. The discovery and investigation has shown that chlorination practice in the conventional system has formed a chlorination by product of Thrihalomethanes (THMs). Experiment conducted on animal provided evidence of the carcinogenity of THMs. Through investigation conducted there is a correlation between the high usage of chlorine and the high formation of THM. In practice the highly polluted raw water needs higher concentration of chlorine in disinfection. In any treatment work disinfection is the most important processes. There are various type of disinfectant available and chlorine system has been used worldwide. This dissertation will discuss the comparison between chlorine in conventional system and a newly introduced system of ozonation in our country but has been used effectively in other countries. Selection of this system is due to the record of effectiveness evaluated. Discussion will be based on the effectiveness of both system and comparing the merit and demerit of both systems.